Covid 19: Humanities- Teaching and Digital Inclusion - Gimenes, Roseli (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2021)
This article proposes to analyse the difficulties of higher education in a Language course due to digital inclusion during the pandemic caused by COVID19. The objective is to consider how remote education improves communication between students and teachers in the teaching-learning process. Methodologically, we analysed some remote classes in a Literature course that applied Active Learning Methodologies in the wake of authors such as Bates (2016), Bergmann (2016) and Ribeiro (2020). Our main contribution is to show how this specific educational moment, caused by the confinement, brought about the digital inclusion of students through new distance or face-to-face methodologies.